BRASSINOSTEROID INSENSITIVE2 Interacts with ABSCISIC ACID INSENSITIVE5 to Mediate the Antagonism of Brassinosteroids to Abscisic Acid during Seed Germination in Arabidopsis . Issue 11 (21st November 2014) - Hu, Yanru; Yu, Diqiu
Abstract : A kinase regulates the integration of brassinosteroid and abscisic acid signaling during seed germination by phosphorylating and stabilizing an abscisic acid-responsive transcription factor. Abstract: Seed germination and postgerminative growth are regulated by a delicate hormonal balance. Abscisic acid (ABA ) represses Arabidopsis thaliana seed germination and postgerminative growth, while brassinosteroids (BRs ) antagonize ABA -mediated inhibition and promote these processes. However, the molecular mechanism underlying BR -repressed ABA signaling remains largely unknown. Here, we show that the Glycogen Synthase Kinase 3-like kinase BRASSINOSTEROID INSENSITIVE2 (BIN2), a critical repressor of BR signaling, positively regulates ABA responses during seed germination and postgerminative growth. Mechanistic investigation revealed that BIN2 physically interacts with ABSCISIC ACID INSENSITIVE5 (ABI5), a bZIP transcription factor. Further genetic analysis demonstrated that the ABA -hypersensitive phenotype of BIN2- overexpressing plants requires ABI5. BIN2 was found to phosphorylate and stabilize ABI5 in the presence of ABA, while application of epibrassinolide (the active form of BRs ) inhibited the regulation of ABI5 by BIN2. Consistently, the ABA -induced accumulation of ABI5 was affected in BIN2- related mutants. Moreover, mutations of the BIN2 phosphorylation sites on ABI5 made the mutant protein respond to ABA improperly. Additionally, the expression of several ABI5 regulons was positively modulated by BIN2. These results provide evidence that BIN2 phosphorylates and stabilizes ABI5 to mediate ABA response during seed germination, while BRs repress the BIN2-ABI5 cascade to antagonize ABA -mediated inhibition.